Design and characterization of novel manganite perovskites Ba1-xBixTi1-xMnxO3 (0≤x≤0.2). Issue 17 (1st December 2020) - Chchiyai, Zakaria; El Bachraoui, Fatima; Tamraoui, Youssef; Bih, Lahcen; Faik, Abdessamad; Alami, Jones; Manoun, Bouchaib
Abstract: Polycrystalline manganite powders of Ba1-x Bix Ti1-x Mnx O3 (x = 0, x = 0.1 and x = 0.2) were synthesized by the conventional solid-state reaction process. Their crystal structure, morphological, optical, dielectric and electrical properties were investigated. X-ray diffraction of the prepared samples was made at room temperature and confirmed the formation of a perovskite phase. Structural refinement, using the Rietveld method, revealed a tetragonal P 4 mm phase of pure BTO and a tetragonal P 4/ mmm phase with the presence of vacancies for both doped samples (x = 0.1 and x = 0.2). Scanning electron microscopy indicated that the perovskite samples had a grain size smaller than 1 μm. From UV–vis–NIR spectra, we found that the band gap reduces from 3.29 eV to 1.48 eV with the increase of Bi and Mn amounts, resulting in a shift of the absorption wavelength region toward the visible range. Dielectric analysis was conducted in a wide range of temperatures at different frequencies. Phase transitions were identified from thermal dielectric results, showing that the samples exhibited a non-relaxor behavior. The structural transformation from tetragonal to cubic structure corresponding to the transition from ferroelectric phase to paraelectric phase was observed in the dielectric properties investigation. The complex impedance spectroscopy indicated the presence of grain and grain boundary effects in the conduction mechanism. Electrical analysis showed that doping with Bi and Mn enhanced the DC conductivity. Furthermore, the DC conductivity temperature dependence confirmed that the studied samples present a semiconductor behavior. The activation energies of grain and grain boundaries depended on the amount of incorporated Bi and Mn. The activation energy of grain varied between 0.54 and 0.87 eV suggesting that the DC electrical conductivity is governed by ionized oxygen vacancies. The activation energy of grain boundaries varied between 0.85 and 0.58 eV.